Design of a Sextuple Band Microstrip Antenna for Wearable Applications a Wban the Low Sar - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a new design of a sextuple band microstrip antenna for wearable applications a WBAN (Wireless Body Area Network) low SAR (Specific Absorption Rate). The proposed antenna consists of L-shaped slots have been determined based on the frequency bands. For the integration of these techniques six frequency bands consisting of the GSM 1.8 GHz, the WLAN standard IEEE 802.11 ah the band 900 MHz, the ISM band 2.4 GHz and 5.7 GHz, and 3.5 GHz band UWB respectively were considered. The proposed antenna is designed with the purpose of obtaining a low SAR models of the human body, considering both the electromagnetic effect and the shell model in human tissues. © 2018 IEEE.